AB0564 Temporal arteritis: is there any correlation between ultrasonographic arterial wall involvement and the inflammatory cellular infiltrate at histological examination?. (15th June 2017) - Germano, G; Macchioni, PL; Cavazza, A; Cimino, L; Muratore, F; Salvarani, C
Abstract : Background: Ultrasonographic alterations such as the halo sign and the compression test are now accepted as surrogate markers of artery inflammation. No data have yet been published on the correlation between the ultrasonographic grading of arterial wall inflammation and the grading of cellular infiltrate. Objectives: To compare a semiquantitative ultrasonographic grading (USG) of TA involvement (halo sign and media-intima thickness) with a semiquantitative grading of the inflammatory burden in patients with giant cell (temporal) arteritis (GCA). Methods: Fiftheen consecutive patients with new onset clinical symptoms and satisfiing ACR criteria for GCA, with positive halo sign in the frontal branch and positive temporal artery biopsy have been enrolled. For each patients we performed power Doppler ultrasonography of temporal artery with a 18–6 MHz linear probe (Esaote MyLab 70) and measured the maximum halo thickness of TA frontal branch in a quantitative and semiquantitave (0–3) grade of involvement (0 = <0.37 mm, 1 = in between 0.38–0.44, 2 = 0.45–0.6 mm, 3 = >0.6). TA biopsy was done in the same frontal branch evalutaed with US. Then we compared the ultrasonographic data with a semiquantitative (0: absent, 1: mild, 2: moderate, 3: severe) grading of the trasmural cellular inflammatory infiltrate and with the intima-media thickness of the TA biopsy specimen. Moreover US results were correlated with the other patterns of histological alterations (giant cells, calcifications, laminar necrosis). Correlation between variables was done by Rho of Spearman method. Results: 15 patients, 6 males and 9 females (mean age 71.6±7 years – duration symptoms at onset 1.7±1.3 months – mean ESR 60 mm/h ±29 – mean CRP 8 mg/dl ± 5.2) entered the study. US halo sign was bilateral in 10/15 (66, 7%). The mean halo thickness was 0.53 mm ± 0.12. Five patients had USG =1, six patients =2 and four patients =3. The hystological inflammatory grade 1 was present in seven pts, grade 2 in four and grade 3 in four pts. No significant correlation were found between USG and histological inflammatory grade, nor with the presence of giant cells, calcifications, laminar necrosis and intima-media thickness. Conclusions: No correlation has been found between the size of the halo sign and the hystological inflammatory grading. Disclosure of Interest: None declared